Social funds : assessing effectiveness. - World Bank. Operations Evaluation Department (Washington, D.C. : World Bank, 2002)
It reviews the development effectiveness of social fund projects and draws implications for future Bank support to them. It responds to the interest of the World Bank's Board of Executive Directors for an independent evaluation of this fast-expanding portfolio. The review is based on an examination of existing data and literature, and brings to bear new information relating to the participatory process in social fund projects and their institutional development impacts at the government, nongovernment, and community levels.
At head of title: World Bank Operations Evaluation Department.
Includes bibliographical references (p. 179-184).
oif 20/02/15
Loan
Keywords: Economic assistance -- Developing countries -- Evaluation; Public works -- Developing countries -- Finance; Infrastructure (Economics) -- Developing countries -- Finance; Developing countries -- Social conditions